2014
DOI: 10.1371/journal.pone.0101220
|View full text |Cite
|
Sign up to set email alerts
|

Diatom-Derived Polyunsaturated Aldehydes Activate Cell Death in Human Cancer Cell Lines but Not Normal Cells

Abstract: Diatoms are an important class of unicellular algae that produce bioactive polyunsaturated aldehydes (PUAs) that induce abortions or malformations in the offspring of invertebrates exposed to them during gestation. Here we compare the effects of the PUAs 2-trans,4-trans-decadienal (DD), 2-trans,4-trans-octadienal (OD) and 2-trans,4-trans-heptadienal (HD) on the adenocarcinoma cell lines lung A549 and colon COLO 205, and the normal lung/brunch epithelial BEAS-2B cell line. Using the viability MTT/Trypan blue as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Decadienal was previously reported to induce apoptosis in mammalian tumour cells (Miralto et al, 1999). These data were recently confirmed by Sansone et al (2014) who demostrated that the PUAs decadienal, heptadienal and octadienal activated cell death in human cancer cell lines but not in normal cells. These authors showed that PUAs had a toxic effect on both A549 and COLO 205 tumor cells but not BEAS-2B normal cells, activating an extrinsic apoptotic machinery in contrast to other anticancer drugs that promote an intrinsic death pathway, without affecting the viability of normal cells from the same tissue type (Sansone et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…Decadienal was previously reported to induce apoptosis in mammalian tumour cells (Miralto et al, 1999). These data were recently confirmed by Sansone et al (2014) who demostrated that the PUAs decadienal, heptadienal and octadienal activated cell death in human cancer cell lines but not in normal cells. These authors showed that PUAs had a toxic effect on both A549 and COLO 205 tumor cells but not BEAS-2B normal cells, activating an extrinsic apoptotic machinery in contrast to other anticancer drugs that promote an intrinsic death pathway, without affecting the viability of normal cells from the same tissue type (Sansone et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…In addition, their clone was not active against bacteria. S. marinoi, as other diatoms, are known to produce a series of secondary metabolites (PUAs and other oxylipins) with anticancer properties (Miralto et al, 1999;Sansone et al, 2014). Considering that all S. marinoi clones produce oxylipins, even if in different amounts (Gerecht et al, 2011), we suggest that the compounds responsible for the observed anticancer and antibacterial activities are not oxylipins because only one clone has anticancer activity.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have shown that the marine carotenoid fucoxanthin found in brown seaweeds and several diatom species has antioxidant, anti-inflammatory, anticancer, antiobese, antidiabetic, antiangiogenic, and antimalarial activities (Peng et al, 2011), and that the fatty alcohol ester nonyl 8acetoxy-6-methyloctanoate (NAMO), isolated from the diatom P. tricornutum, has anticancer effects on three different cancer cell lines including human leukemia (HL-60) and lung carcinoma (A549), and a mouse melanoma (B16F10; Samarakoon et al, 2014). In addition to these, diatom unsaturated aldehydes such as decadienal, octadienal, and heptadienal isolated from Skeletonema marinoi have shown anticancer effects in lung cancer A549 and colon COLO 205 tumor cells, without affecting the viability of normal cells from the same tissue type (Sansone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Study on structure-activity relationship of oxylipins has revealed that the double bond geometry E/Z has no effects on inhibiting the development of embryos of sea urchin egg while the inhibition is primarily due to the chain length, the α, β, γ, δ-unsaturated aldehyde element, and the side chain polarity of PUAs (Adolph et al, 2003). Moreover, the biological importance of PUAs has been increasingly noted for their antimitotic and proapoptotic properties (Nappez et al, 1996), anti-inflammatory activity (Girona et al, 1997), anti-cancer activity (Sansone et al, 2014) and antimicrobial properties (Paul and Fenical, 1986).…”
Section: Oxylipinsmentioning
confidence: 99%